Dietary Hyaluronic Acid Migrates into the Skin of Rats. (14th October 2014) - Oe, Mariko; Mitsugi, Koichi; Odanaka, Wataru; Yoshida, Hideto; Matsuoka, Ryosuke; Seino, Satoshi; Kanemitsu, Tomoyuki; Masuda, Yasunobu
Abstract : Hyaluronic acid is a constituent of the skin and helps to maintain hydration. The oral intake of hyaluronic acid increases water in the horny layer as demonstrated by human trials, but in vivo kinetics has not been shown. This study confirmed the absorption, migration, and excretion of 14 C-labeled hyaluronic acid ( 14 C-hyaluronic acid). 14 C-hyaluronic acid was orally or intravenously administered to male SD rats aged 7 to 8 weeks. Plasma radioactivity after oral administration showed the highest level 8 hours after administration, and orally administered 14 C-hyaluronic acid was found in the blood. Approximately 90% of 14 C-hyaluronic acid was absorbed from the digestive tract and used as an energy source or a structural constituent of tissues based on tests of the urine, feces, expired air, and cadaver up to 168 hours (one week) after administration. The autoradiographic results suggested that radioactivity was distributed systematically and then reduced over time. The radioactivity was higher in the skin than in the blood at 24 and 96 hours after administration. The results show the possibility that orally administered hyaluronic acid migrated into the skin. No excessive accumulation was observed and more than 90% of the hyaluronic acid was excreted in expired air or urine.